Texture analysis in a rare case of tibial intraosseous lipoma - Totaro, Marilina; De Falco Alfano, Daniele; Negri, Francesco; Seletti, Valeria; Paladini, Ilaria; Russo, Giuseppe; Mostardi, Maurizio; Ganazzoli, Chiara; Gafà, Veronica; Corrado, Michele; Giganti, Melchiore (Acta Biomedica Atenei Parmensis, 2016)
Intraosseous lipoma is a very rare lesion, accounting for only 0.1% of all primary osseous tumors (1), first described in 1980 (2). This lesion is considered the rarest of benign bone tumors (3); probably it is not the actual incidence because these lesions are frequently asymptomatic and the introduction of cross-sectional imaging, especially MRI, seems to have increased the detection (4). The majority of intraosseus lipomas are in the lower limbs (70%) and the os calcis being the most frequently involved (32%). Most cases reported in literature have an age of 40 years (5). Tumor texture could be measured from medical images that provide a non-invasive method of capturing intratumoral heterogeneity and could potentially enable a prior assessment of a patient. Some Authors recently proposed Texture analysis to characterize musculoskeletal lesions (6). For the first time we measured the tumoral texture from Magnetic Resonance images in tibial intraosseous lipoma in a 29-years-old female.